Modelling the factors of agile practices in project management A case of illumination project organization - K, Gayathr; Suresh, M (International Journal of Engineering and Technology, 2018)
Project management involves various activities which contribute for achieving specific goals and success criteria. The illumination compa-nies involved in project management and related fields face major issues because of rapid changes in technology and environment. The solu-tion to this issue will be to establish a flexible and quick environment in the organization which is easily adaptable to the changes in the ex-ternal environment. In this paper the various factors that influence agile project management in an illumination company has been identified. The Interpretive Structural Modelling (ISM) has been used to analyse the interrelationships among the factors. Finally, the paper concludes that the most influential factors are supervisory behaviours, employee involvement, domain expertise, nature of management.Â Â